2004
DOI: 10.1161/01.cir.0000124581.18191.15
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Does Not Affect the Antiplatelet Potency of Clopidogrel When It Is Administered Concomitantly for 5 Weeks in Patients With Acute Coronary Syndromes

Abstract: Background-The antiplatelet effect of clopidogrel may be attenuated by short-term coadministration of lipophilic statins.We investigated whether the coadministration of atorvastatin for 5 weeks in patients with acute coronary syndromes (ACS) could affect the antiplatelet potency of clopidogrel. Methods and Results-Forty-five hypercholesterolemic patients with the first episode of an ACS were included in the study. Patients were randomized to receive daily either 10 mg of atorvastatin (nϭ21) or 40 mg of pravast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…87 Interference with clopidogrel metabolism by other drugs that are frequently given to patients with atherosclerosis, such as atorvastatin, 86,88 can increase the number of patients who are resistant to clopidogrel, although this is still a controversial issue. 89,90 Clinical Consequences A recent study of 60 patients undergoing coronary angioplasty confirmed the high interindividual variability of platelet inhibition by clopidogrel and showed that patients with clopidogrel resistance (mean ADP-induced platelet aggregation on day 6 of treatmentϭ103Ϯ8% of baseline) are at increased risk for recurrent cardiovascular events. 91 …”
Section: Clopidogrel Resistancementioning
confidence: 97%
“…87 Interference with clopidogrel metabolism by other drugs that are frequently given to patients with atherosclerosis, such as atorvastatin, 86,88 can increase the number of patients who are resistant to clopidogrel, although this is still a controversial issue. 89,90 Clinical Consequences A recent study of 60 patients undergoing coronary angioplasty confirmed the high interindividual variability of platelet inhibition by clopidogrel and showed that patients with clopidogrel resistance (mean ADP-induced platelet aggregation on day 6 of treatmentϭ103Ϯ8% of baseline) are at increased risk for recurrent cardiovascular events. 91 …”
Section: Clopidogrel Resistancementioning
confidence: 97%
“…Lau et al [63] showed that atorvastatin promoted clopidogrel resistance at 10 mg, 20 mg and 40 mg (P = 0.027, P = 0.002 and P = 0.001, respectively). On the other hand, Mitsios et al [64] reported that daily doses of 10 mg of atorvastatin did not result in a decreased clopidogrel response over a 5-wk period. In the same study, clopidogrel significantly attenuated platelet aggregation in 3 different concentrations of ADP in the presence of no statin, atorvastatin, or pravastatin (P < 0.01, P < 0.01, and P < 0.02 at 2 μmol, 5 μmol, and 10 μmol of ADP, respectively).…”
Section: Clopidogrel Resistancementioning
confidence: 98%
“…14 Although a potential drug interaction be-tween clopidogrel and atorvastatin was suspected on the basis of the inhibition of clopidogrel activation by atorvastatin via its effects on CYP3A4, 15,16 more recent data question the clinical significance of this interaction. 17,18 Atorvastatin and fluvastatin have minimal renal excretion, and dose adjustment of these statins in patients with renal insufficiency is therefore unnecessary. 19 Although it was initially suspected that gemfibrozil increased statin levels by inhibiting CYP450 enzymes, it is now thought that its inhibition of glucuronidation of statins may be a likely culprit.…”
Section: Statin Safetymentioning
confidence: 99%